Fish in the lakes, wild rice, and game in abundance : testimony on behalf of Mille Lacs Ojibwe hunting and fishing rights - McClurken, James M.; Cleland, Charles E., 1936- (Book collections on Project MUSE., 2000)
How does one argue the Native side of the case when all historical documentation was written by non-Natives? The Mille Lacs selected six scholars to testify for them.